Teaching quality assessment in higher education institution within the context of students’ perceptions of teachers (sociological study experience) - I. . Zelenev; S. . Tumanov (Высшее образование в России)
The empirical basis of the paper is formed by the findings of the survey of the students ofone of the departments of Moscow State University conducted by the Institute for Complex Research in Education of the Lomonosov Moscow State University. Students’ perceptions of the teachers are analyzed with regard to the impact on them of the economic and symbolic factors of identity (within the frames of the graded model of the stages of perception). Possibility of the content interpretation of the students’ assessments of their teachers is suggested to theorganizers of the educational process as a part of the teaching quality monitoring.